Mapping Colombians' positions on sentencing for substance offenses - Daniel del Rio Forero; Claudia Pineda Marín; María Teresa Muñoz Sastre; Lonzozou Kpanake; Etienne Mullet (BMC, 2022)
Abstract Background In Colombia, a person caught in possession of an illicit substance is not judicially sanctioned as long as the quantity does not exceed the maximum allowable amounts. Given that the public is divided on the appropriateness of this policy, an examination of the various public positions was undertaken. Method A convenience sample of 302 adults were presented with 48 vignettes depicting a situation of everyday life easily recognizable by all in Colombia; that of a male person who is apprehended in the street by the police because he is suspected of illicit trafficking. These vignettes were created by orthogonal variation of four factors: Type of substance, amount of substance, type of charge against the offender, and offender's age. Results Through cluster analysis, six qualitatively different positions were found. These positions corresponded to three distinct, classical philosophies (a) a libertarian, free-market philosophy - punishment should never be extremely severe because the trade in psychotropic substances is a trade like any other (6%), (b) a moralistic, conservative philosophy - punishment should always be extremely severe except perhaps in certain cases (52%), and (c) a progressive, human rights-inspired philosophy - punishment should always be proportional to the seriousness of the facts (42%). Conclusion Half of Colombian people supported a control policy according to which the use of psychotropic substances is considered profoundly immoral. Most of the other segment of the population express views similar to those of international organizations. It is therefore desirable that legislators rely on progressive international legislation to support domestic policies that are not strictly moralistic and conservative.